Characteristic identification of seismogenic electromagnetic anomalies based on station electromagnetic impedance - Fan, Ye; Hu, Wenbao; Han, Bing; Tang, Ji; Wang, Xiao; Ye, Qing (Frontiers in Earth Science, 2023)
The main components of seismo-electromagnetic research are the deep underground electromagnetic seismogenic environment, electromagnetic field changes at different stages of the seismogenic process, and the physical mechanism and change rules of electromagnetic properties of the earth’s interior. Traditional electric and magnetic methods mainly analyze the single field change of the geoelectric field, geomagnetic field, or resistivity at frequencies less than 1Hz. These do not include the extremely low-frequency band that is sensitive to seismic events, so it is difficult to obtain the characteristics of time-spatial variations and propagation characteristics precursors. In comparison, magnetotelluric stations observe magnetotelluric fields containing seismogenic-induced electromagnetic disturbances, and the observation frequency band is wide. In this paper, the three-dimensional numerical simulation method is used to calculate the magnetotelluric apparent resistivity anomaly generated by resistivity changes in the seismogenic zone, and the forward algorithm of arbitrarily orientated dipole source in layered earth is used to simulate the response of low-frequency pre-earthquake electromagnetic radiation. The magnetotelluric response including seismogenic resistivity anomaly and pre-earthquake electromagnetic radiation is obtained using the field component composition method. The frequency characteristics and spatial distribution characteristics of apparent resistivity anomalies are systematically analyzed, and the results are of important significance for the observation, data processing, and identification and analysis of seismic electromagnetic anomalies in different seismogenic processes.